Significação e design - Cauduro, Flávio Vinícius (Em Questão, 2010)
Signification is a social practice which produces and reproduces meanings, the result of that being the sign (signum facere), artificial semantic differences constructed by predicative subjects of a cultural formation. In order for the designer to be able to formulate relevant design solutions, he/she has to reject what is considered already known, as well as a prioristic premises, dichotomized positions and reductive definitions. That will allow him/her to think creatively about his/her practical problems. Innovative solutions do not follow the excludent philosophy of either/or but adopt instead the inclusiveness of this and that, something that seems to explain the closeness of contemporary design philosophies to Peirce’s semiotics, which is what this paper aims to show.